2005
DOI: 10.1002/pssc.200461148
|View full text |Cite
|
Sign up to set email alerts
|

Phased array operation of nanocrystalline porous silicon ultrasonic emitters

Abstract: To confirm the applicability of thermally induced ultrasound emission from nanocrystalline porous silicon (nc-PS) devices as directional sound emitter, the radiation pattern of one-dimensionally arrayed nc-PS device have been investigated. The nc-PS emitter is fabricated on a p-type Si substrate by conventional electrochemical anodization with subsequent formation of the surface electrode. It is shown that the emission pattern of arrayed devices can be controlled due to flat nature of the frequency response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…1 Many experimental investigations on this phenomenon and its application were carried out, regarding various aspects of TA ultrasound, such as characteristics, intensification, radiation pressure, three-dimensional image sensing, phased array and impulse operation, and sound reproduction, which show that thermo-acoustic ultrasound has lots of advantages over traditional electric-acoustic ultrasound due to its unique nature −− wideband flat frequency response: larger frequency bandwidth and acoustic pressure, lesser reverberation and distortion, higher sensing accuracy and spatial resolution, easily integrated in MEMs and sound signal self-demodulation, and availability and controllability for finely structured phase arrays operation. [2][3][4][5][6][7][8][9][10][11][12][13] However, theoretical investigation of TA emission seriously lags behind the experimental one due to comparatively fewer efforts. Currently, alomast all the formulas for calculating TA emission so far are one-dimensional, 1,[14][15][16][17]19,22 taking advantage of the plane-wave solution based on the pressure-temperature coupled equations in a fluid given by F. A. McDonald and G. C. Wetsel, Jr., 18 and the problems of near-and far-field TA emission need to be dealt with seperately.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many experimental investigations on this phenomenon and its application were carried out, regarding various aspects of TA ultrasound, such as characteristics, intensification, radiation pressure, three-dimensional image sensing, phased array and impulse operation, and sound reproduction, which show that thermo-acoustic ultrasound has lots of advantages over traditional electric-acoustic ultrasound due to its unique nature −− wideband flat frequency response: larger frequency bandwidth and acoustic pressure, lesser reverberation and distortion, higher sensing accuracy and spatial resolution, easily integrated in MEMs and sound signal self-demodulation, and availability and controllability for finely structured phase arrays operation. [2][3][4][5][6][7][8][9][10][11][12][13] However, theoretical investigation of TA emission seriously lags behind the experimental one due to comparatively fewer efforts. Currently, alomast all the formulas for calculating TA emission so far are one-dimensional, 1,[14][15][16][17]19,22 taking advantage of the plane-wave solution based on the pressure-temperature coupled equations in a fluid given by F. A. McDonald and G. C. Wetsel, Jr., 18 and the problems of near-and far-field TA emission need to be dealt with seperately.…”
Section: Introductionmentioning
confidence: 99%
“…All of these attractive merits are mainly attributed to its unique nature-constant ͑flat͒ amplitude-frequency response over a wide frequency range. [2][3][4][5][6][7][8][9] However, compared with lots of experimental studies, theoretical investigations of this characteristic are very few. After Shinoda et al presented a formula for PS thermal-ultrasonic emission by utilizing the fundamental equations of McDonald and Wetsel's photoacoustic model, Boullosa and Santillán also derived an expression from thermal piston model for ultrasound radiation from TA transducer.…”
mentioning
confidence: 97%
“…thus based on the above-mentioned theory, Wang studied the characteristics and regularities of ultra-sound from spherical focusing TA emitter in detail 17 . J. Hirota et al investigated the emission characteristics of TA emission from one-dimensional porous silicon arrays and showed that the directivity of TA waves can be achieved by changing the frequency of the input current 18 . B. Gelloz et al arranged nine porous silicon TA emission surfaces into a 3 X 3 array to study the effect of changes in emission frequency and phase on the directivity of its TA emission, and concluded that proper adjustment of the size of the array element, the density of the array, as well as the relationship between the input frequency and the phase can be realised by concentrating and adjusting the direction of the emission density 19 .…”
Section: Introductionmentioning
confidence: 99%